Pengembangan Keterampilan 4Cs Pada Pembelajaran IPS SD Dalam Materi Perubahan Sosial Budaya - Mira Juliya; Tin Rustini; Yona Wahyuningsih (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2021)
The purpose of writing this article is to analyze the development of 4Cs skills in social studies learning in elementary schools in terms of socio-cultural change. The method of writing articles used is literature study or literature review using secondary data sources collected through textbooks, e-books, scientific journals, and so on. Testing the validity of the data using stages consisting of data collection, data reduction, data presentation, and concluding. The results of writing this article explain that. The development of 4Cs skills in elementary social studies material socio-cultural change can be done with various strategies, models, and methods that are relevant to the development of 4Cs skills. This using Problem Based Learning (PBL), Project-Based Learning (PjBL), Cooperative Learning, interview methods, and various other learning strategies. Problem Based Learning (PBL) strategies can be used to develop skills in critical thinking processes and problem-solving, Project Based Learning (PjBL) can be used to develop student's skills to create and innovate, interview methods can be used to develop student's communication skills and the whole of these strategies can also be used in developing students collaboration skills.